In praise of snapshots - Ravi Kanbur (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
The conventional justification for moving from income distribution to intergenerational mobility analysis is that the movie encompasses the snapshot and is normatively superior as the basis for assessing policy. Such a perspective underpins many an argument for shifting the focus from income redistribution, which is said to equalize outcomes, to equalizing opportunity by increasing mobility through such policies as equal provision of public education. This paper argues that this perspective can be misleading. It shows that normative evaluation of mobility in any event often falls back on a snapshot perspective. Further, the snapshot itself often contains the seeds of the movie, as posited in the Great Gatsby Curve. Income redistribution can itself improve mobility even if that is the only objective. The paper thus speaks in praise of snapshots.
Keywords: I24; I31; J6; 330; income mobility; snapshots; income redistribution; Great Gatsby Curve; education policy